Searching for the 'X' factor: investigating the genetics of primary ovarian insufficiency - Anya Knight; Sara Sugin; Andrea Jurisicova (BMC, 2024)
Abstract Primary ovarian insufficiency (POI) is the cessation of ovarian function before the age of 40. The causes of POI are heterogeneous, but substantial evidence exists to support a genetic basis of POI, particularly in the critical involvement of genes on the X chromosome. Recent studies have revealed novel candidate genes through the identification of copy number variations associated with POI. This review summarizes the genes located on the X chromosome with variants shown to be associated with POI in humans and/or in mice. Additionally, we present evidence to support the potential involvement of these candidate genes in the etiology of POI. We conducted a literature search in PubMed to identify case studies and screenings for the genetic causes of POI. We then performed systematic searches for the proposed candidate genes to investigate their potential reproductive roles. Of the X-linked candidate genes investigated, 10 were found to have variants associated with cases of POI in humans. An additional 10 genes were found to play a supportive role in POI. Other genes were not implicated in any cases of POI but were associated with various roles in reproduction. In the majority of cases where variants were identified through whole-exome sequencing, rather than targeted screening of candidate genes, more than one genetic variant was identified. Overall, this review supports past findings that the X chromosome plays a critical role in ovarian function, as demonstrated by a link between POI and various disruptions to genes on the X chromosome. Current genetic screening for POI, which includes only FMR1, is inadequate to capture the majority of cases with a genetic origin. An expanded genetic testing may improve health outcomes for individuals with POI as it could lead to better early interventions and education about these health risks.